Reconfiguring health care professions - Dent, Mike; Radcliffe, James (International Journal of Public Sector Management., 2003)
This special edition of IJPSM focuses on the implications of managementreforms for the medical, nursing and allied professions. These health careprofessionals within the public sector have been challenged by change, and arebeing reconfigured by a number of factors, not least political pressures andgovernment regulation.